2019
DOI: 10.3390/ijms20235989
|View full text |Cite
|
Sign up to set email alerts
|

Epicardial Adipose Tissue: Clinical Biomarker of Cardio-Metabolic Risk

Abstract: Epicardial adipose tissue (EAT) is part of the visceral adipose tissue (VAT) that surrounds the heart and it is a quantifiable, modifiable, and multifaceted tissue that has both local and systemic effects. When EAT is enlarged, EAT contributes to atherosclerotic cardiovascular disease (ASCVD) risk and plays a role in the development of metabolic syndrome (MetS). In this review, we will discuss the role of EAT in various facets of MetS, including type 2 diabetes mellitus (T2DM) and insulin resistance. We examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
112
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(119 citation statements)
references
References 99 publications
3
112
0
4
Order By: Relevance
“…Visceral and subcutaneous adipose tissues differ in accumulation and metabolism and the relationship between EAT and anthropometric parameters is still debated. Our and other groups previously reported that EAT increase is independent from BMI in patients with cardiovascular diseases (Parisi et al, 2015;Villasante Fricke and Iacobellis, 2019).…”
Section: Discussionsupporting
confidence: 60%
“…Visceral and subcutaneous adipose tissues differ in accumulation and metabolism and the relationship between EAT and anthropometric parameters is still debated. Our and other groups previously reported that EAT increase is independent from BMI in patients with cardiovascular diseases (Parisi et al, 2015;Villasante Fricke and Iacobellis, 2019).…”
Section: Discussionsupporting
confidence: 60%
“…Moreover, it has been proposed that the adipokines released by EAT in pathological conditions have paracrine effects on cardiac electrical activity, affecting conductivity and promoting atrial fibrillation [ 20 ], and in coronary arteries, they cause atherosclerosis through the promotion of inflammation and immune cell infiltration [ 21 , 22 ]. Lately, EAT thickness has been considered a clinical biomarker that correlates to features of heart failure and metabolic syndrome [ 23 , 24 , 25 , 26 , 27 ]. Another fat depot that surrounds the coronary arteries is the perivascular adipose tissue (PVAT).…”
Section: Adipose Tissue Dysfunction and Cvdsmentioning
confidence: 99%
“…This is due to the intimate connection between the myocardium and a peculiar VAT depot, known as epicardial fat [74][75][76], as there is no fascia muscle separating their anatomical layer walls [75]. In dysfunctional epicardial fat, the release of pro-inflammatory adipokines, including tumor necrosis factor (TNF)-α, interleukin (IL)-6, leptin and monocyte chemoattractant protein-1 (MCP-1) [77], contributes to worsening the atherogenic processes affecting the coronary arteries and myocardium [77]. Moreover, there is a growing interest in the characterization of the immune fat lineage in obese patients.…”
Section: Cardiac-fat Diseases Ruled By Opnmentioning
confidence: 99%